Analisa Nilai Investasi Penjualan Rumah Tipe 36 Pada Perumahan PT. Rahayu Charani Rosend: Analysis Of Investment Value For The Sale Of 36 Type Houses At PT. Rahayu Charani Rosend Housing - Larasati, Diah Ayufitria; Respati, Rida (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Increasing demand for affordable housing presents investment opportunities, but requires further research to understand the ability of lower-middle-class communities to afford such housing. The property business is identified as a crucial investment, especially with growing populations and increasingly scarce and expensive land over time. This indicates that the demand for new homes will continue to rise, especially in developing countries and large cities. Critical investment analysis was conducted to provide information to PT. Rahayu Charani Rosend regarding potential profits and risks. This research utilized the Net Present Value (NPV), Profitability Index (IP), Payback Period (PP), and Break Even Point (BEP) methods. Data used included selling prices, housing price lists, and bank interest rates for the year 2023. The research results show an NPV of Rp13,146,894 > 0, an IP value of 4.806 > 1, a PP of 1 month 61 days, and a BEP at 11 units (BEP in Indonesian rupiah equivalent to Rp1,883,601,297). Based on these calculations, it can be concluded that this investment is viable because NPV > 0 and IP > 1.